Evaluation of microbial contamination in the light-curing composite used by dental students in their clinical practices - Bedoya-Correa, Claudia-María; Sarrazola-Moncada, Ángela-María; Palacio-Espinosa, Sandra-Milena; Julio-Madrid, Olga-Lucia; Osorio-Rojo, Natalia-Andrea; Garzón-Henao, Astrid-Julieth (Revista Estomatología, 2016)
Background: Some procedures that are performed during the daily dental practice might favor environmental contamination by microorganisms. Therefore, their presence in materials that are routinely used in the dental office constitutes a risk of transmitting pathogen agents, thereby causing cross-contamination.Aim: To evaluate microbial contamination of light-curing composites previously used in patients at the School of Dentistry, Universidad Cooperativa de Colombia, Envigado campus.Materials and Methods: The experimental group consisted of 46 composite samples extracted from previously-used composite syringes. Composite from two as-received syringes and two sterile toothpicks were used as the control group. Samples were deposited in BHI broth for 48 hours at 37°C. After this time, a turbidity reading was performed. Contaminated samples were seeded in solid culture media and colonies were described according to their macro and microscopic characteristics. The SPSS 21.0 statistical software was used and Chi-square coefficient was calculated.Results: 34.8% of composites were contaminated by Staphylococcus sp and Gram positive bacillus. No statistical significant differences between composite contamination and frequency of use were observed (p>0,05). Conclusions: Composite microbial contamination after a single use was demonstrated. Therefore, composite remnants contained in previously-used syringes might be responsible for cross-contamination.